ANALISIS KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH DI DESA TULO’A KECAMATAN BULANGO UTARA KABUPATEN BONE BOLANGO - Madjowa, Nona Fitriana; Bakhtiar, Bakhtiar; Fuad, Mohammad Januar; Yusuf, Iswandi (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2024)
The aim of this research is to analyze the demand and availability of water in Tulo'a village, North Bulango sub-district, Bone Bolango Regency. This study uses secondary data in the form of daily rainfall for 5 years from 1 rain station. The method used for water availability uses the empirical equation from Ffolliot and for the projected water needs of the population, namely the Geometric, Arithmetic, Exponential Method. Based on the results of the analysis of the amount of water availability in 2030, it is 6,008,933.70 m3/year and the demand for clean water is 1,576,289.00m3/year so that it can be said that it is still in the water surplus category.